A carbon-doped tantalum dioxyfluoride as a superior electron transport material for high performance organic optoelectronics. (April 2020) - Vasilopoulou, Maria; Yusoff, Abd Rashid Bin Mohd; Kuganathan, Navaratnarajah; Bao, Xichang; Verykios, Apostolis; Polydorou, Ermioni; Armadorou, Konstantina-Kalliopi; Soultati, Anastasia; Papadimitropoulos, Georgios; Haider, Muhammad Irfan; Fakharuddin, Azhar; Palilis, Leonidas C.; et al.
Abstract: The design and development of novel materials with superior charge transport capabilities plays an essential role for advancing the performance of electronic devices. Ternary and doped oxides can be potentially explored because of their tailored electronic energy levels, exceptional physical properties, high electrical conductivity, excellent robustness and enhanced chemical stability. Here, a route for improving metal oxide characteristics is proposed by preparing a novel ternary oxide, namely, carbon-doped tantalum dioxyfluoride (TaO2 FCx ) through a straightforward synthetic route and exploring its effectiveness as an electron transport material in optoelectronic devices based on organic semiconductors. Among other devices, we fabricated fluorescent green organic light emitting diodes with current efficiencies of 16.53 cd/A and single-junction non-fullerene organic solar cells reaching power conversion efficiencies of 14.14% when using the novel oxide as electron transport material. Our devices also exhibited the additional advantage of high operational and temporal stability. Non-fullerene OSCs based on the novel compound showed unprecedented stability when exposed to UV light in air due to the non-defective nature of TaO2 FCx. We employed a tank of experiments combined with theoretical calculations to unravel the performance merits of this novel compound. This study reveals that properly engineered ternary oxides, in particular, TaO2 FCx or analogous materials can enable efficient electron transport in organic optoelectronics and are proposed as an attractive route for the broader field of optoelectronic devices including metal-organic perovskite, colloidal quantum dot and silicon optoelectronics. Graphical abstract: A superior electron transport material namely carbon-doped tantalum dioxyfluoride for optoelectronic applications was developed. The novel compound exhibited ideal energetic alignment with organic semiconductors, low refractive index and high conductivity hence achieving current efficiencies reaching 16.53 cd/A in OLEDs and power conversion efficiencies of up to 14.14% in non-fullerene OSCs with the additional advantage of high operational and temporal stability. Image 1 Highlights: Design and development of a carbon-doped tantalum dioxyfluoride as electron transport material. The novel oxide exhibits high electron conductivity, high transparency, low refractive index and high hydrophobicity. Fluorescent green OLEDs with current efficiencies of 16.53 cd/A. Single-junction non-fullerene OSCs reaching PCEs of 14.14 %.